ORTEGA Y GASSET: NO CAMINHO DA HIPERMODERNIDADE.UMA VISÃO PROJETIVA DA CONTEMPORANEIDADE - CARLOS GOMES (Ideas y Valores)
This article aims to establish a philosophical and cultural understanding of the most representative ideas of contemporary feeling and existence. In the works of the spanish philosopher José Ortega y Gasset (1893-1955), which is one prominent Iberian thinker, there exists a very interesting projective reflection of the figure of culture in the twentieth century, in consonance with Oswald Spengler's pessimistic thought. What they both have in common is the existential need to decipher the signs of the times we live in. Because of this, Ortega recovers common philosophical and sociogical topics such as life, massification, hedonism, and nihilism, which Gilles Lipovetsky uses in order to ground the new paradigm of hypermodernity based on artistic (trans-aesthetic) capitalism.